Neuronal cdc2-like kinase: a cdc2-related protein kinase with predominantly neuronal expression. - Hellmich, M R (1992)
Recent studies have shown that there exists a family of protein kinases structurally and functionally related to the yeast cell cycle regulatory kinase cdc2 [Meyerson, M., Faha, B., Su, L.-K., Harlow, E. & Tsai, L.-H. (1991) Cold Spring Harbor Symp. Quant. Biol. 56, 177-186 and Meyerson, M., Enders, G. H., Wu, C.-L., Su, L.-K., Gorka, C., Nelson, C., Harlow, E. & Tsai, L.-H. (1992) EMBO J. 11, 2909-2917]. Two members of cdc2 family, p34cdc2 (also named cdk1) and cdk2, have been identified in mammalian cells. cdk1 kinase regulates the progression from G2 to M phase, and cdk2 kinase has been proposed to regulate the progression from G1 to S phase. In this work, we have cloned and structurally characterized a third member of the cdc2 kinase family with 58% amino acid sequence identity to mouse cdk1 and 61% identity to human cdk2. We call this kinase neuronal cdc2-like kinase (nclk) because, in contrast to either cdk1 or cdk2, nclk is expressed at high levels in terminally differentiated neurons no longer in the cell cycle. Previous studies have shown [Hisanaga, S., Kusubata, M., Okumura, E. & Kishimoto, T. (1991) J. Biol. Chem. 266, 21798-21803 and Guan, R. J., Hall, F. L. & Cohlberg, J. A. (1992) J. Neurochem. 58, 1365-1371] that cdk1 kinase, but not other structurally defined protein kinases, could phosphorylate the repeated Lys-Ser-Pro (KSP) motifs found in mammalian high and middle molecular mass neurofilament subunits in vitro, but the precise molecular nature of the endogenous neuronal KSP kinase has remained undefined. The structural similarity of nclk to cdk1 kinase and its high level of expression in terminally differentiated neurons suggest that nclk may play a role in the phosphorylation of the neurofilament KSP repeats in vivo, a function distinct from cell cycle regulation.